Taxation, Inflation, and Interest Rates - Tanzi, Vito.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1984)
The volume is made up of nine studies, some dealing with purely theoretical aspects, others with purely empirical ones, and still others dealing with both.
Includes bibliographies and indexes.
osc 29/6/17
Loans
Keywords: Taxation; Interest rates